English Language Teachers’ Experiences of Using ICT in Online Teaching - Bhandari, Bhimlal (Vox Batauli, 2023)
After COVID-19 pandemic, online learning has predominated over traditional face-to-face instruction. Education was one of the most affected areas during the COVID-19 pandemic. This study aims at investigating university level English language teachers' experiences of using ICT in online teaching. The study intends to examine teachers’ perceived benefits and challenges of using ICT tools in online mode of teaching. For this purpose, I selected 80 English language teachers from sixteen campuses of Rupandehi. I used quantitative survey research design for the study. I collected data through closed-ended questionnaire only. This investigation demonstrates the satisfactory experiences of English language teachers in using ICT in online teaching. Use of ICT can facilitate and make teaching easier maximizing the learner autonomy, transferring traditional mode of teaching in learning English. Lack of basic ICT knowledge and skills, the digital divide, and students' laziness were some of the challenges of using ICT. Moreover, ICT use in online teaching can contribute learners to work in their own pace; provide a new platform of learning by expanding the access of resources in learning system.